Advanced Excel for scientific data analysis - Levie, Robert de (Oxford University Press, 2008)
Combining an easy-going style with an emphasis on practical applications, this greatly expanded second edition is remarkable in scope and coverage. As reviews of the first edition noted, the term "advanced" in the title is not used lightly. Less than a third of its 700+ pages are devoted to least squares analysis, yet the reader will learn about many aspects of this ubiquitous method that are seldom found together in one volume: multivariate and polynomial centering, the statistical uncertainty in uncertainty estimates, how to use the covariance, singular value decomposition, the pros and cons of weighted least squares, moving equidistant least squares, nonlinear least squares, and imprecision contours